Antibacterial and Cytotoxicity characteristics of experimental epoxy -based endodontic sealer loaded with silver gold nanoparticles: in vitro study - Nermine Hassan; Mona Riad; Shereen Hafez Ibrahim; Khaled Mahmoud; Bassam Ahmed Abulnoor; Reham Hassan (BDJ Open)
Abstract Background Enhancing the antibacterial capabilities of dental materials by adding nanoparticles has been the subject of some research. However, the potential toxic effect of this material on the vital tissues should be investigated to avoid additional damage to the tissue. Objective This study aimed to validate the long-term cytotoxic and antibacterial properties of an epoxy resin-based endodontic sealer (AH Plus) with and without loading with silver gold nanoparticles (Nano Care Plus Silver Gold®). Material and methods The tested groups were Nano Care Gold (group I), modified resin sealer (m AH Plus; group II) and AH Plus served as a control group (group III). Agar diffusion was used to measure the antibacterial activity against Enterococcus faecalis. Using the MTT test, cytotoxicity assessment was carried out in accordance with ISO-10993-5 guidelines to assess the cells’ viability as soon as possible and after two and four weeks. The t-test was used to statistically examine the data. The chosen significance threshold was P <0.05. Results Antibacterial results revealed that there was no difference in the diameter of the inhibition zones measured in all groups at 24 h. While in 48 and 72 h, the difference was statistically significant (p <0.05). In 48-h Nanogold was significantly higher than AH Plus when tested alone (p <0.05), however their mixture showed insignificant difference. After 72 h, the Nano gold was significantly higher than that of AH Plus & Nano gold mixture (p <0.05). Cytotoxicity result revealed there was a significant difference between tested groups at different intervals (p <0.001). For immediate measurements, values measured with the AH group were significantly higher than those of other groups (p <0.001). For the AH& nanogold group, there was no significant difference between values measured at different intervals (p = 0.578). Conclusions Silver gold nanoparticles have acceptable antibacterial properties and low cytotoxicity to be used as canal pretreatment prior to the application of the sealer or even incorporated with AH Plus sealer.